School urinary screening program in Japan: history, outcomes, perspectives - Masataka Honda; Takeshi Yanagihara; Yoshimitsu Gotoh (The Korean Society of Nephrology, 2024)
In Japan, pediatric urinary screening in schools for asymptomatic hematuria and proteinuria began in 1974 and has been very successful in detecting asymptomatic kidney diseases at an early stage. While the American Academy of Pediatrics recommended discontinuing urinalysis as a public health service in 2007, urinary screening in Japan has proven extremely successful in reducing the incidence of kidney failure with replacement therapy in children and young adults, especially through the early treatment of glomerulonephritis, such as immunoglobulin A nephropathy. Furthermore, the positivity rate on urinary screening in Japan is significantly lower than in the United States where the rate of false positive results is typically very high. Japan's seamless and efficient pediatric urinary screening may be a helpful example for other countries as well. However, the present investigation revealed several, unresolved problems with the system. For example, the methods used varied in terms of their cutoff point, additional examinations, and types of detailed testing. In Japan, various urinary screening methods are being tested to optimize the system for national use. Recently, the authors also recommended a system of detailed examinations, including beta-2 microglobulin testing and ultrasonography, to detect congenital anomalies of the kidney and urinary tract, the most common, underlying disease in kidney failure with replacement therapy, which is often overlooked until the symptoms have become grave. While school urinary screening has been ongoing for about 50 years and should be continued, improvements should also be made to it as needed.